Dokazovanje v postopku odločanja o odvzemu premoženjske koristi in premoženja - Gorkič, Primož (Pravnik, 2014)
Last amendments to Criminal Code and its provisions on criminal forfeiture have significantly altered its scope. The paper focuses on procedural implications of recent developments in Slovenian law, drawing from different solutions adopted in substantive criminal law that require different procedural outlines. The paper deals with issues of presumption of innocence, standards of proof, accusatory principle and discretionary powers of the courts. Special attention goes to newly introduced forms of extended confiscation. Their procedural implications have been scrutinised in the light of ECtHR case-law and relevant comparative solutions.
Keywords: dokazi; kazniva dejanja; zaplemba premoženja